Effect of phosphorus and potassium on the growth and yield of French bean - Karim, Saedy; Uddin, F. M. Jamil; Rashid, Harun Or; Hadiuzzaman, Mohammad (Journal of Scientific Agriculture, 2020)
An experiment was conducted at the Agronomy Field Laboratory of the Department of Agronomy, Bangladesh Agricultural University, Mymensingh to investigate the yield response of French bean (Phaseolus vulgaris L.) as affected by phosphorus and potassium management. The experiment consisted of two factors. Factor A: Phosphorus fertilizer (4 levels) viz. P1=15Kg P ha-1, P2=20 Kg P ha-1 and P3=25 Kg P ha-1 , P4=35 Kg P ha-1 and factor B: Potassium fertilizer (4 levels) viz. K1=0 Kg K ha-1, K2=20 Kg K ha-1, K3=30 Kg K ha-1 and K4=40 Kg K ha-1. The variety BARI Jharsheem-3 was used in this experiment as the test crop. The experiment was laid out in a randomized complete block design (RCBD) with three replications. In case of phosphorus @ 25 kg ha-1 the highest number of pods plant-1 (4.96), pod length (13.34 cm), number of seeds pod-1 (4.54), weight of 1000-seed (431.21 g), seed yield (1.33 t ha-1), stover yield (1.53 t ha-1), biological yield (2.86 t ha-1) and harvest index 46.50% were found. In case of potassium @ 40 kg ha-1, he highest number of pods plant-1 (5.80), pod length (14.89 cm), number of seeds pod-1 (4.24), weight of 1000-seed (430.37 g), seed yield (1.53 t ha-1 ), stover yield (1.46 t ha-1 ), biological yield (2.99 t ha-1) and harvest index 51.17% were found. Interaction effect of phosphorus and potassium the highest number of pods plant-1 (5.18), pod length (13.40 cm), number of seeds pod-1 (4.30), weight of 1000-seed (430.53 g), seed yield (1.40 t ha-1 ), stover yield (1.60 t ha-1 ), biological yield (3.00 t ha-1 ) and harvest index 46.66% were recorded from P @ 25 kg ha-1 and K @ 40 kg ha-1. However, from the study it can be concluded that application of P @ 25 kg ha-1 and K @ 40 kg ha-1 was the most suitable combination for better yield of French bean.